An Examination of Performance of First Year Students at an Ontario University: An Admission Perspective - Allan, Lorraine G.; Darling, Alexander L.; Hughes, Robert C.; Rosenfeld, Jack M. (Canadian Journal of Higher Education, 1983)
Major changes in the Ontario secondary school system over the last 15 years have increased the concerns within some universities about the use of Grade 13 marks as the principal criterion for evaluating applicants. These concerns focus on grade inflation, variability of marks among schools, and how appropriate some subjects are for university admission. This paper reports on a study of these issues conducted at McMaster University. The relationship between Grade 13 admission and Year I university averages was examined. Two issues that have received little attention elsewhere were also examined: how Year I performance varied by applicant status, and the relationship between individual Grade 13 subjects and Year I performance. The results indicate that Grade 13 marks, which are the only measure of a student's achievement available, continue to be a reasonable predictor of subsequent performance in Year I. Grade 13 subjects were identified that were more consistently associated with Year I performance than others. There was also evidence that some Grade 13 subjects may be contributing to an "inflated" admission average. The results of this study should be useful in evaluating existing admission policies and in the development of the new Ontario Academic Courses.